2009
DOI: 10.1002/cne.22081
|View full text |Cite
|
Sign up to set email alerts
|

Collateral projections of neurons in laminae I, III, and IV of rat spinal cord to thalamus, periaqueductal gray matter, and lateral parabrachial area

Abstract: Projection neurons in lamina I, together with those in laminae III–IV that express the neurokinin 1 receptor (NK1r), form a major route through which nociceptive information reaches the brain. Axons of these cells innervate various targets, including thalamus, periaqueductal gray matter (PAG), and lateral parabrachial area (LPb), and many cells project to more than one target. The aims of this study were to quantify projections from cervical enlargement to PAG and LPb, to determine the proportion of spinothala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
102
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 68 publications
(148 reference statements)
9
102
0
Order By: Relevance
“…The main axon in these cells bifurcated within the dorsal grey matter and while one branch followed the regular path of PNs, the other one entered the dorsal funiculus and ascended there in the ipsilateral side. Lamina I PNs with collaterals crossing the midline at the supraspinal level and thus achieving bilateral projections have been reported before (Al-Khater and Todd, 2009). In case of the four bilateral projection neurons in our sample the splitting of the main axon occurs earlier and the two equally strong branches seemingly ascend in different tracts from the beginning.…”
Section: Bilaterally Projecting Axonssupporting
confidence: 61%
“…The main axon in these cells bifurcated within the dorsal grey matter and while one branch followed the regular path of PNs, the other one entered the dorsal funiculus and ascended there in the ipsilateral side. Lamina I PNs with collaterals crossing the midline at the supraspinal level and thus achieving bilateral projections have been reported before (Al-Khater and Todd, 2009). In case of the four bilateral projection neurons in our sample the splitting of the main axon occurs earlier and the two equally strong branches seemingly ascend in different tracts from the beginning.…”
Section: Bilaterally Projecting Axonssupporting
confidence: 61%
“…We observed retrogradely labeled neurons to be located predominantly in the superficial dorsal horn at upper cervical (C1-2) and caudal medullary levels following Fluorogold injections in the lateral parabrachial nucleus or ventral posteromedial thalamus, confirming recent studies in mice [15], and rats [9; 10]. Using a double-label strategy, we observed that 89% of spinoparabrachial and 94% of spinothalamic projections neurons co-expressed NK1R.…”
Section: Discussionsupporting
confidence: 87%
“…The PB, in turn, provides rapid access to forebrain limbic structures, including the amygdala and hypothalamus, which are presumed to contribute to the emotional quality of the pain experience. Other spinal cord projection neurons target the midbrain periaqueductal gray (PAG), reticular formation, hypothalamus and thalamus (Bernard et al, 1995; Burstein et al, 1990; Todd et al, 2000) and many spinal cord projection neurons collateralize to multiple supraspinal sites (Al-Khater and Todd, 2009; Spike et al, 2003). As to neurochemistry, most PB-projecting neurons (~80%) express the neurokinin 1 receptor (NK1), which is targeted by substance P-expressing primary afferent nociceptors (SP; (Ding et al, 1995; Todd et al, 1998) as well as SP-expressing local interneurons.…”
Section: Introductionmentioning
confidence: 99%